2019
DOI: 10.1016/j.jjcc.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Field termination-of-resuscitation rule for refractory out-of-hospital cardiac arrests in Japan

Abstract: Background: Guidelines for cardiopulmonary resuscitation (CPR) recommend using the universal termination-of-resuscitation (TOR) rule to identify out-of-hospital cardiac arrest (OHCA) patients eligible for field termination of resuscitation, thus avoiding medically futile transportation to the hospital. However, in Japan, emergency medical services (EMS) personnel are forbidden from terminating CPR in the field and transport almost all patients with OHCA to hospitals. We aimed to develop and validate a novel TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…The lower specificity could hypothetically be driven by patients surviving with an impaired neurologic status. 49 However, as not all studies report on neurologic outcome, these results should be interpreted with caution and the exact cause of the lower specificity remains to be elucidated.…”
Section: Diagnostic Performancementioning
confidence: 97%
See 2 more Smart Citations
“…The lower specificity could hypothetically be driven by patients surviving with an impaired neurologic status. 49 However, as not all studies report on neurologic outcome, these results should be interpreted with caution and the exact cause of the lower specificity remains to be elucidated.…”
Section: Diagnostic Performancementioning
confidence: 97%
“…Previous studies showed that chances of falsely recommending TOR decrease with increasing time to TOR-assessment. 19,38,45 For example, patients without ROSC/defibrillation after 5 min have higher survival chances than after 20 min, and therefore early application of the rule may result in undesired termination-advice. Asian regions often apply a scoop-andrun strategy, with short in-field CPR-duration (2À4 min.…”
Section: Diagnostic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Studies Reporting the Derivation and Internal Validation of a TOR Rule to Predict Poor Neurological Outcome. We identified very low-certainty evidence (downgraded for risk of bias, inconsistency, indirectness, and imprecision) from 6 nonrandomized studies 57,58,61,66,74,80 These studies derived and internally validated 12 distinct TOR rules to predict poor neurological outcome. Studies by Haukoos et al, 61 Lee et al, 66 Shibahashi et al, 74 and Yoon et al 80 derived multiple TOR rules.…”
Section: Studies Reporting Clinical Validation Of a Tor Rule To Predictmentioning
confidence: 99%
“…Cardiac arrest treatments are based on the Japanese CPR guidelines [5]. Most patients in OHCA are treated by EMS personnel, transported to a hospital, and registered in the All-Japan Utstein registry [17], because EMS providers are not basically permitted to terminate resuscitation in the field, except in cases involving victims of decapitation, incineration, decomposition, rigor mortis, or dependent cyanosis.…”
Section: Ems Systems In Japanmentioning
confidence: 99%